Implementasi Penguatan Profil Pelajar Pancasia yang Berkebhinekaan Global di dalam kelas SMP Advent Remboken - Tio Jernita Sinaga; Apeles Lexi Lonto; Julien Biringan (CV. Kurnia Grup, 2026)
This study aims to examine the implementation of Strengthening the Pancasila Student Profile, especially in the global diversity dimension, in learning activities in the Remboken Adventist Junior High School classroom. The research focuses on the importance of applying the global diversity dimension, the form of implementation carried out in the learning process, and its influence on students' attitudes and behaviors. The method used in this study is a qualitative approach with data collection techniques through observation, interviews, and documentation. Data sources are obtained from teachers and students which are then analyzed through the stages of data reduction, data presentation, and conclusion drawing and verification. The results of the study show that strengthening the Pancasila Student Profile in the global diversity dimension has an important role in creating a conducive, tolerant, and inclusive learning environment. The implementation of these values is carried out through the integration of Pancasila values in learning activities, habituation of mutual respect, the implementation of religious activities, class deliberations, group work, and the provision of examples by teachers in daily life. The impact of the implementation can be seen in the increasing tolerance of students, the ability to communicate in the midst of diversity, the growth of a sense of responsibility, and awareness to maintain harmony in the school environment. However, this study also found several obstacles, including the limitation of educators who have a background in Pancasila and Citizenship Education and the need to strengthen consistency in program implementation. Thus, the implementation of the Pancasila Student Profile Strengthening which emphasizes the global diversity dimension at Remboken Adventist Junior High School has made a positive contribution to the formation of the character of students who are tolerant, have a strong national identity, and are able to coexist harmoniously in a diverse society.